AS‐IL6 promotes glioma cell invasion by inducing H3K27Ac enrichment at the IL6 promoter and activating IL6 transcription. Issue 24 (2nd December 2016) - Wang, Yu; Chen, Xiaoyu; Tang, Guodong; Liu, Dingyang; Peng, Gang; Ma, Wenbin; Liu, Qing; Yuan, Jian
Abstract : Interleukin‐6 (IL‐6) is widely expressed in a variety of malignant tumors; thus, targeting the IL‐6/STAT3 pathway represents a promising therapeutic strategy for malignant cancers. In this study, we identified a noncoding RNA, AS‐IL6, which is transcribed antisense to IL6 and induces IL6 expression in glioma cells. Knockdown of AS‐IL6 attenuates LPS‐induced IL6 transcription. Interestingly, AS‐IL6 does not change IL6 mRNA stability, but induces the enrichment of histone H3 acetylated at lysine 27 (H3K27Ac) at the IL6 promoter. In addition, we found that depletion of AS‐IL6 inhibits the invasive ability of glioblastoma cells, while treatment of cells with recombinant IL6 reverses this effect. Our results reveal a novel mechanism of IL6 regulation and demonstrate an oncogenic role for AS‐IL6 in glioma cells. Abstract :